2021
DOI: 10.1021/acs.jpclett.1c03395
|View full text |Cite
|
Sign up to set email alerts
|

Accurate Simulations of the Reaction of H2on a Curved Pt Crystal through Machine Learning

Abstract: Theoretical studies on molecule–metal surface reactions have so far been limited to small surface unit cells due to computational costs. Here, for the first time molecular dynamics simulations on very large surface unit cells at the level of density functional theory are performed, allowing a direct comparison to experiments performed on a curved crystal. Specifically, the reaction of D 2 on a curved Pt crystal is investigated with a neural network potential (NNP). The developed NNP is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 69 publications
0
12
0
Order By: Relevance
“…98 Furthermore, recent work has shown that this DF can reproduce experiments of D 2 on chemically related curved Pt crystals with (111) terraces and (100) steps with chemical accuracy. 105 The barrier height reported for PBEα57-vdW-DF2 was −0.008 eV. We retain this value as the reference value (see Table 2), even though it was set to 0.0 eV in the previous SBH10 database.…”
Section: Ii3a Dissociative Chemisorption Of H 2 On Transition Metals ...mentioning
confidence: 99%
“…98 Furthermore, recent work has shown that this DF can reproduce experiments of D 2 on chemically related curved Pt crystals with (111) terraces and (100) steps with chemical accuracy. 105 The barrier height reported for PBEα57-vdW-DF2 was −0.008 eV. We retain this value as the reference value (see Table 2), even though it was set to 0.0 eV in the previous SBH10 database.…”
Section: Ii3a Dissociative Chemisorption Of H 2 On Transition Metals ...mentioning
confidence: 99%
“…Given the ease with which QCT simulations can be carried out the present work suggests that they are a meaningful approach for understanding the dynamics of atom plus diatom reactions and for larger systems as well. QCT-based approaches have also been used for the reaction of H 2 on platinum surfaces, 75 the formation of CO 2 on amorphous solid water, 70,71 CO adsorbed on NaCl, 76 and for investigating photodissociation reactions of larger molecules such as acetaldehyde or the syn-Criegee intermediate. 77,78…”
Section: Discussionmentioning
confidence: 99%
“…For complex surface structures with a wide variety of dynamic reactive sites, it is highly nontrivial to replace ab initio methods with cheaper and more scalable methods. Previously, cluster expansions [5] and empirical [6] / machine-learned (ML) [7] force fields have been employed. These methods rely only on the atomic positions in local environments and do not explicitly consider the electronic structure, thereby scaling linearly with the number of atoms 𝑂 (𝑁 atom ) and providing several orders-of-magnitude acceleration compared to DFT.…”
Section: Performance Attributesmentioning
confidence: 99%
“…On noble metals such as Pt, an H 2 molecule approaches the Pt surface and dissociates to form two chemisorbed H atoms, which diffuse and eventually recombine and desorb from the surface as molecular H 2 (Figure 1) [10]. A variety of force field-based methods have been employed to model H/Pt, most notably ReaxFF [11], embedded-atom method (EAM) [12], tight-binding [13], low-dimensional models [14], and ML force fields [7]. Empirical models such as ReaxFF and EAM have been shown to be inaccurate and unreliable for high-temperature long-timescale simulations [15].…”
Section: Performance Attributesmentioning
confidence: 99%
See 1 more Smart Citation